Cell division method for numerical simulation of wetting and drying in hydrodynamic models with unstructured grids - Yuan, Lirong (Frontiers in Marine Science, 2025)
Periodic wetting and drying occur extensively in many shallow water systems such as coastal wetlands. Proper description of the wetting and drying front (WDF) is a challenge for hydrodynamic models of these systems and yet it is essential for accurate simulations of flow and transport processes within them. In this study, we developed a wetting and drying algorithm with cell division method to track the WDF on three-dimensional unstructured grids of a finite volume-based hydrodynamic model. An inundation function was introduced to determine intersections of the moving WDF with sides of elements at the boundary. These front-associated, partially wetted elements were simulated simultaneously with fully wetted elements with full consideration of the WDF’s movement and its influence on local mass and momentum balance so as to guarantee the overall flow continuity and mass conservation. Test simulations with benchmark cases were conducted to compare the performances of the new algorithm and a traditional method. The results demonstrated the improvement achieved by the improved method in terms of mass conservation, and proper simulations of the WDF and bed friction effects in near-front areas. The improved method exhibits superiority in dealing with high-order nonlinear flow and transport processes in coastal salt marsh system because it solves momentum equations in partially wetted cells. Although it was implemented within a finite-volume model, the improved algorithm, in principle, can be applied to hydrodynamic models based on other numerical methods.